2015
DOI: 10.1002/lary.25139
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic identification and monitoring of the external branch of superior laryngeal nerve during thyroidectomy

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Novel intraoperative nerve monitoring (IONM) for laryngeal nerves is being developed and may reduce the risk of UVFP following thyroid surgery. 21,22 Regularly performing IONM during thyroid surgery was suggested, but its cost-effectiveness remains unclear. 23 A more effective application of IONM is reasonable in patients with higher risks.…”
Section: Results From Ahn Et Al Showed That the Uvfp Rate Ismentioning
confidence: 99%
“…Novel intraoperative nerve monitoring (IONM) for laryngeal nerves is being developed and may reduce the risk of UVFP following thyroid surgery. 21,22 Regularly performing IONM during thyroid surgery was suggested, but its cost-effectiveness remains unclear. 23 A more effective application of IONM is reasonable in patients with higher risks.…”
Section: Results From Ahn Et Al Showed That the Uvfp Rate Ismentioning
confidence: 99%
“…Kandil et al (23) reported lower mean EMG amplitudes for EBSLN comparing with RLN in their study in 2015. Similarly, in our study, we observed lower mean EMG amplitudes for EBLSN.…”
Section: Discussionmentioning
confidence: 77%
“…No todos los centros asistenciales disponen del neuroestimulador para individualizar el nervio, de todos modos e independientemente de este detalle, el conocimiento de la anatomía topográfica del RLNLS es vital para su reconocimiento. El uso del neuroestimulador logra un mayor individualización del nervio y se nutre mejor del aporte brindado por la clasificación de Friedman (Aina & Hisham;Friedman et al;Kandil et al, 2015;Arun et al, 2016;Ekhar et al;Bruno;Gurleyik et al, 2019).…”
Section: Discussionunclassified